Obesity: could evolution be responsible? - Ernő Duda (Cardiologia Hungarica)
Humans have demonstrated remarkable endurance and adaptability to extreme environments thanks to their superior cognitive abilities and physical capabilities. Over thousands of years, Homo sapiens developed numerous traits that were highly advantageous for survival. During the last quarter of a million years, they became the dominant species on Earth due to special characteristics that evolved over millions of years. While ancient civilizations transformed people's lifestyles, they only impacted a small fraction of humanity. Even within empires, most individuals led nomadic lives until the late medieval period. Since World War II, most people's physical and social conditions have changed rapidly and dramatically. However, our genetics, physiology, and anatomy have not kept pace with these changes. Consequently, some once advantageous traits now become unfavorable or even harmful. The abundance of food, coupled with our ancient instincts, has led to an obesity epidemic in many countries. This has resulted in health issues such as atherosclerotic cardiovascular disease, type 2 diabetes due to insulin resistance, and metabolic dysfunction-associated steatotic liver disease or steatohepatitis. To maintain the health of our nomadic bodies in a “civilized” environment, we need to move much more and learn to manage some of our primal instincts.